Nano-opto-mechanical actuator driven by gradient optical force - Cai, H. (2013)
In this letter, a nanoscale opto-mechanical actuator driven by gradient optical force is designed and demonstrated. The nanoscale actuator can achieve a maximum displacement of 67 nm with a response time of 94.5 ns. The optical force is estimated as 1.01 pN/μm/mW in C-band operating wavelengths. The device is fabricated on silicon-on-insulator wafer using standard dry etching processes. Compared with traditional microelectromechanical systems actuators driven by electrostatic force, the nanoscale opto-mechanical actuator has the advantages of high resolution of actuation, nanoscale displacement, and fast operating speed. It has potential applications in optical signal processing, chemical, and biological sensing.